If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 3y = 1 Solving 6x + 3y = 1 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3y' to each side of the equation. 6x + 3y + -3y = 1 + -3y Combine like terms: 3y + -3y = 0 6x + 0 = 1 + -3y 6x = 1 + -3y Divide each side by '6'. x = 0.1666666667 + -0.5y Simplifying x = 0.1666666667 + -0.5y
| -5(-7+5x)=-190 | | 5y-1+y+51=6y+50-2y | | -4(2p+4)-25=5(4p+3) | | 109x+17=77x+25 | | 5p+4=4p+11 | | 12x=204 | | 35+3y=110 | | 2t=7-1 | | -5e^6+5e^4=0 | | 2(c-3)=3(c-4) | | n+39=52 | | x+3y=110 | | -8x=120 | | 3(7-y)-y=5 | | -49+16y+9=4(5y-4)-4 | | 5(c-5)+4=2+c-23 | | 5x+9=51-10x | | -x-7=3x-7 | | 2-5x=10+3x | | 101-3x=5x+15 | | y=1.6214x+1.1143 | | 3x+4x-x+x= | | -2x+15=-6x-1 | | -19-5x=11-9x | | 98-6x=10x-18 | | x=7/5y | | -2x=22 | | 0.4s+15=s | | 0.4s+15=a | | 12-7x=11x+17 | | 3x+9=4x+7 | | 6t-24t=24+1 |